Trump Administration’s Initiatives in Resolving North Korea’s Nuclear Problem: Cooperative Threat Reduction (CTR) Approach - Kim, Youngshik; Han, Chonghee (International Journal of Emerging Trends in Social Sciences, 2018)
The purpose of the paper is to review the applicability of the Cooperative Threat Reduction (CTR), the so-called Nunn-Lugar program to North Korea in an effort to denuclearize the country. To this end, it focuses on analysis of some US scholars and experts’ initiatives on that program based on lessons learned from the former Soviet Union to set the ground rules for resolving North Korea’s nuclear issues because the US has been a salient country able to serve as an engine of non-proliferation and expertise that can be used around world. This article argues that the ground rules should be built in terms of clarifying the concept of threats, identifying the means of strike capability, and choosing the participants and their roles in the negotiation in order to increase the possibility of success for the CTR program on North Korea. In line with these principles, US-Republic of Korea (ROK) coordination would be crucial, despite of obstacles like DPRK’s objection of ROK’s involvement in this process of bilateral engagement between US and DPRK. The ROK would need to be more actively engaged in the CTR program with the help of financial resources as well as technical assistance that could make a soft landing for North Korea’s CTR program, as the Korean Energy Development Organization (KEDO) during the mid-1990s envisioned. It is more likely to apply this approach to North Korea’s nuclear program and to achieve a good result in resolving North Korean nuclear problems by the active participation of the two co-sponsor and co-initiator of CTR model, Nunn and Lugar, into the discussions in the administration of President Trump.